THE EFFECT OF MAGNETITE (Fe3O4)CATALYST FROM IRON SANDS ON DESORPTION TEMPERATURE OF MgH2 HYDROGEN STORAGE MATERIAL - Maulinda Maulinda; zulkarnain Jalil; Adi Rahwanto (Universitas Syiah Kuala, 2016)
One of the future technologies for a safe hydrogen storage media is metal hydrides. Currently, Mg-based metal hydride has a safety factor and efficient for vehicle applications. However, the thermodynamic properties of magnesium hydride (MgH2) found a relatively high temperature. High desorption temperatures caused MgH2 high thermodynamic stability resulting desorption enthalpy is also high. In this study, natural mineral (iron ore) has been extracted from iron sand into powder of magnetite (Fe3O4) and used as a catalyst in an effort to improve the desorption properties of MgH2. Magnetie has been successfully extracted from iron sand using precipitation method with a purity of 85 % , where the purity of the iron sand before extracted was 81%. Then, MgH2-Fe3O4 was milling using mechanical alloying method with a variety of catalysts and milling time. The observation by XRD showed the material was reduced to nanocrystalline scale. MgH2 phase appears as the main phase. DSC test results showed with the addition of Fe3O4, the desorption temperature can be reduced up to 366oC, compared to pure pure MgH2 reached by 409o C. Furthermore, based on gravimetric test, the hydrogen release occurs at a temperature of 388o C, weight loss of 0.66 mg during 16 minutes.